In-silico approach to investigate death domains associated with nano-particle-mediated cellular responses. (August 2018) - Banu, Hussaina; Joseph, Maria Christina; Nisar, Mokashi Nida
Graphical abstract: Highlights: Death Domain superfamily of nanoparticle mediated inflammation-apoptosis studied. NALP3 inflammasome complex in-silico study critical as proteins aggregate in-vitro. NALP3 interaction with ASC & ASC2 proteins compared using MD simulation & Docking. Z-scores, binding energies and key amino acid residues at binding pockets compared. Binding studies shows NALP3 in proximity with ASC than ASC2 protein. Abstract: The current research is based on computational study of the Death Domain (DD) superfamily of proteins involved in the cytoplasmic inflammasome complexes associated with apoptosis and inflammation in response to the nanoparticle treatment. The PYD domains of the DD superfamily proteins, NALP3 and ASC, were chosen for investigation as they are found to be primarily involved in the regulation of innate immunity and are associated with apoptosis and inflammation. The in-vitro studies of these proteins have proven to be a challenge as the proteins have a tendency to aggregate under laboratory conditions. The interactions between PYD-PYD domains of NALP3 & ASC proteins as well as PYD-PYD domains of NALP3 and ASC2 proteins were studied using the computational tools. In our study, the protein structures were taken from Protein Data Bank, and molecular dynamics simulation was performed using NAMD software followed by molecular docking studies using HADDOCK. The generated protein models were validated using PROCHECK and then the protein-protein interactions were analyzed using the molecular visualization tool CHIMERA. We noticed that the affinity between PYD of NALP3-ASC complex is better when compared to the NALP3-ASC2 complex based on their binding energies and docking scores. In the case of NALP3-ASC complex, seven key amino acids of ASC-PYD protein interface interact with four key amino acids of NALP3-PYD protein interface. However, in the case of NALP3-ASC2 complex, six key amino acids of ASC-PYD protein interact with four key amino acids of NALP3-PYD protein. Although, there is not much difference in the number of interacting amino acid residues between the two protein complexes, we understand that the NALP3-ASC exhibits better binding interaction and stability than the NALP3-ASC2 protein complex because the number of hydrogen bonding between them is more when compared to the latter. The hydrogen bonds between the interacting amino acids of the NALP3-ASC protein interface are 12, whereas it is 6 in the case of NALP3-ASC2 protein interaction. The protein-protein interaction seems to be dominated by the energetically significant hydrogen bonding followed by the electrostatic interaction in the NALP3-ASC protein interface, whereas both hydrogen bonding and the interaction between charged residues appears to play a significant role at the NALP3-ASC2 protein interfaces.